Pattern of Antibiotic Consumption in Two Italian Production Chains Differing by the Endemic Status for Porcine Reproductive and Respiratory Syndrome - Trevisi, Paolo; Amatucci, Laura; Ruggeri, Roberta; Romanelli, Costanza; Sandri, Giampietro; Luise, Diana; Canali, Massimo; Bosi, Paolo (Frontiers in Veterinary Science, 2022)
The aim of this case study was to quantify antibiotic (AB) use in Italian weaning (W) and fattening (F) units differentiated for Porcine Reproductive and Respiratory Syndrome (PRRS) occurrence. Farms were classified as either PRRS negative (-) or PRRS positive (+) based on the circulation of the virus among the animals. In all the farms, the modified live PRRS virus (PRRSV) vaccine was provided to all the animals. In the PRRS- farms, the level of circulating antibodies was low, and the disease, in its clinical form, did not occur. In the PRRS+ farms, the level of circulating antibodies against the virus was high, and the disease was recurrent. Data regarding AB consumption were collected from 2017 to 2020, and the active compounds (ACs) were expressed as mg of AC/total kg of body weight (BW) produced. Each AC was classified into one of four categories according to the European Medicines Agency classification of ABs for prudent and responsible use in animals: Avoid, Restrict, Caution and Prudence. Data regarding the ACs in each category were analyzed using a linear model which included production phase, PRRS status and their interaction as factors. Performance parameters, average age of the pigs at the end of each phase, daily live weight gain, feed to gain ratio, total losses, cost index and medication costs were significantly influenced by the PRRS chain. The use of class B ABs was not affected by production phase or PRRS status. Conversely, for class C ABs, interaction between the two factors (P=0.02) was observed; W/PRRS+ and F/PRRS+ showed the greatest AB use for this class (P=0.003). For class D ABs, the interaction was significant (P=0.01); class C and D ABs were used more in the weaning (P=0.07) than in the fattening phase (P=0.003). For the weaning phase, the use of class C and D ABs was greater in the PRRS+ than in the PRRS- chain (P<0.01). In conclusion, PRRS status affected the growth of pigs and economic performance. Moreover, PRRS status significantly influenced the use of ABs during all the growing periods with the greatest impact being on the weaning phase.